An environmentally friendly conductive cement-based material curing agent and its preparation method and application
By using modified lithium slag powder, regenerated micro powder and carbon fiber in cement-based material curing agent, the problem of slow hardening time of cement-based material curing agent is solved, and the stability and crack resistance of cured soil are improved, achieving effective utilization of lithium slag and environmental protection.
Patent Information
- Application Number
- CN202410636977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The existing cement-based material curing agents have slow hardening time during winter construction and are difficult to utilize lithium slag, resulting in environmental pollution and waste of resources.
The environmentally friendly conductive cement-based material curing agent with modified lithium slag powder, regenerated micro powder, carbon fiber and cement as the main components is used. By combining modified lithium slag powder and regenerated micro powder, the conductivity and crack resistance of the curing agent are improved and the hydration process is promoted.
It significantly improves the hydration speed of the solidified soil, shortens the construction period, enhances the stability and crack resistance of the solidified soil, and solves the problems of difficulty in using lithium slag and environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an environmentally friendly conductive cement-based material curing agent and a preparation method and application thereof. Background Art
[0002] Cement curing agent is mainly composed of cement, fly ash powder and other raw materials, and is widely used in highway roadbeds, subbases, etc. It is of great significance to improve the strength of cement curing agent and expand its practical application in foundation reinforcement, aeolian sand solidification and other fields. At present, the strength of cement curing agent is mainly improved by adding additives, such as slag powder, natural ore, high-strength fiber, etc.
[0003] At present, the resource utilization of construction waste mainly uses recycled aggregates to prepare inorganic mixtures, recycled bricks, recycled blocks, and a small amount is used in recycled mortar and recycled concrete. At present, this type of research has been relatively systematic and occupies a dominant position in the resource utilization of construction waste. From the perspective of policy, resource acquisition and production and manufacturing costs, the cost of recycled aggregates is not competitive compared with natural materials. Many researchers have begun to explore the development of high-value-added resource products for the preparation of recycled micropowders. Recycled micropowders are fine powders that are obtained by multi-stage sorting, step-by-step crushing, and grinding of waste concrete, waste clay bricks, etc. to a certain fineness. The unhydrated cement particles in the waste concrete and the glass phase and amorphous substances generated during the sintering of clay in the waste clay bricks are ground to a certain fineness and can be used as mineral admixtures for concrete and mortar to exert their filling effect and activity effect. At present, much research has been conducted on the composition and other properties of recycled micropowder and its effects on the mechanical properties and durability of concrete. However, due to the porous nature and rough surface of recycled micropowder itself, the amount of concrete admixtures and water used is high, and the workability loss is large, which limits its large-scale application in commercial concrete. The solution to this technical problem is of great significance.
[0004] With the booming development of new energy vehicles and other industries, the production demand for lithium batteries and other materials is increasing. Lithium slag is a kind of waste residue produced in the production of lithium carbonate. The production of one ton of lithium carbonate produces about 8 to 10 tons of lithium slag. According to statistics, the annual discharge of lithium slag in my country is about 8×10 5 10,000 tons. Due to the high sulfate content, high water absorption rate and low activity in lithium slag, the utilization of lithium slag is difficult and limited. Therefore, lithium slag has become one of the main industrial waste slags discharged in my country. However, how to treat the large-scale lithium slag in a scientific and environmentally friendly way is still a major problem that troubles many scholars.
[0005] Chinese patent CN117069400A discloses a low-carbon cement prepared by using modified lithium slag composite multi-source solid waste, as well as a method and application. The patent uses lithium slag as a raw material for preparing low-carbon cement, modifies it, and combines multi-source solid waste, cement clinker, and stimulant to prepare a low-carbon cement with low preparation cost and strong mechanical properties. The preparation method adopted in the patent can not only alleviate resource shortages, reduce production costs, realize solid waste resource utilization, reduction and harmless treatment, and achieve sustainable development; the low-carbon cement prepared by the patent is significantly improved in flexural and compressive strength, and can greatly enhance the strength in these two aspects according to the change of time; and with the increase in the amount of modified lithium slag added, the strength in flexural and compressive strength is gradually increased, which can be widely used in building materials, pavement materials, cement bodies, and curing agents. However, the modification steps for lithium slag in the patent are high-temperature calcination, grinding, and neutralization with NaOH solution, but the components in the waste lithium slag are not modified. Summary of the invention
[0006] The purpose of the present invention is to provide an environmentally friendly conductive cement-based material curing agent and its preparation method and application in order to solve the shortcomings of the current cement-based material curing agent in the slow hardening time during winter construction. In combination with the problems of lithium slag being difficult to use and seriously wasted in the prior art and the characteristics of the regenerated micropowder itself, the environmentally friendly conductive cement-based material curing agent described in the present invention uses modified lithium slag powder, regenerated micropowder, carbon fiber, and cement as main components, and utilizes lithium slag and regenerated micropowder as resources, which can improve the hydration process and crack resistance of the solidified soil, and greatly improve the stability of the concrete. It aims to solve the problems of industrial by-products such as lithium slag and construction waste polluting the environment and slow hydration of solidified soil in winter construction in the prior art, and further improve the strength and stability of the solidified soil.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] An environmentally friendly conductive cement-based material curing agent comprises the following components in parts by weight:
[0009]
[0010]
[0011] The modified lithium slag powder comprises the following components by mass percentage:
[0012] CaO 60-65%, MgO 1-2%, SiO2 5-10%, Li2O 2%-3%, Fe2O3 0.5%-2.0%, Al2O3 0.1%-1.0% and inevitable impurities, the sum of the mass percentages of CaO, MgO, SiO2, Fe2O3, Al2O3, Li2O and impurities is 100%.
[0013] Furthermore, the cement is P·O 42.5 cement, 300m 2 / kg≤Specific surface area≤370m 2 / kg.
[0014] Furthermore, the average particle diameter of the modified lithium slag powder is 20-50 μm.
[0015] Furthermore, the regenerated fine powder is powdered construction waste with a particle size of ≤0.16 mm generated during the particle shaping process of construction solid waste and collected by a dust collector.
[0016] The regenerated fine powder is mainly composed of crushed rock cement, coarse aggregate and fine aggregate.
[0017] In the above, the regenerated micro powder comprises the following components by mass percentage:
[0018] CaO 45-50%, MgO 1-2%, SiO2 30-35%, Fe2O3 2%-4.0%, Al2O3 5%-10% and inevitable impurities, the sum of the mass percentages of CaO, MgO, SiO2, Fe2O3, Al2O3 and impurities is 100%.
[0019] Furthermore, the carbon fiber has a carbon content greater than 90%, a diameter range of 5-10 microns, and a resistivity range of 2×10^ -6 Ω·cm, and it has good electrical conductivity.
[0020] Furthermore, the exciter is composed of the following components in parts by weight:
[0021] 30-50 parts of sodium hydroxide,
[0022] 180-220 parts of water glass.
[0023] Furthermore, in the above, the purity of the sodium hydroxide is 99.50wt%.
[0024] Furthermore, in the above, the concentration of the water glass is 40wt%, and the modulus is 1.4-2, preferably 1.4.
[0025] Furthermore, the water is ordinary city tap water.
[0026] Furthermore, the environmentally friendly conductive cement-based material curing agent comprises the following components in parts by weight:
[0027]
[0028]
[0029] In addition, the present invention also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0030] S1, preparing modified lithium slag powder;
[0031] S2. Weigh cement, modified lithium slag powder, recycled micro powder, carbon fiber, activator and water according to the mix ratio;
[0032] S3, stirring and dissolving the activator and water to obtain an activator solution;
[0033] S4, mixing cement, modified lithium slag powder, recycled micro powder and carbon fiber to obtain raw materials;
[0034] S5. Stir and mix the activator solution obtained in step S3 and the raw materials obtained in step S4 to obtain an environmentally friendly conductive cement-based material curing agent.
[0035] Furthermore, in step S1, the method for preparing modified lithium slag powder is as follows:
[0036] The waste lithium slag after producing lithium carbonate is successively acidified with hydrochloric acid, evaporated and crystallized, purified with carbonic acid, calcined, and finally ground into powder.
[0037] Furthermore, the method for preparing the modified lithium slag powder is as follows:
[0038] The waste lithium slag after the production of lithium carbonate is reacted in a hydrochloric acid solution environment to generate lithium chloride, and then the solution after the reaction is evaporated and crystallized, and the crystals obtained by evaporation are fully reacted with carbonic acid to obtain purified lithium carbonate. Finally, the lithium slag containing lithium carbonate is calcined at high temperature to decompose the lithium carbonate to obtain lithium oxide. At the same time, the calcium, aluminum and other salts contained in it are decomposed to generate alkaline oxides such as calcium oxide and aluminum, and finally ground to obtain modified lithium slag powder, and finally ground to prepare it.
[0039] Furthermore, the purpose of the evaporative crystallization is to precipitate more lithium chloride.
[0040] In the above, the calcination temperature is 1000-1400°C, preferably 1000°C;
[0041] The calcination time can be determined according to the calcium oxide content in the modified lithium slag after calcination. When the calcium oxide content is 60-65%, the calcination is finished.
[0042] In the above, the grinding is as follows: the waste lithium slag after acidification and calcination is fed into a ball mill for grinding, and the ground modified lithium slag powder is passed through a 120-mesh sieve.
[0043] Furthermore, in step S3, step S4 and step S5, the stirring time is 2 to 4 minutes, preferably 3 minutes.
[0044] The stirring speed is 180-300 r / min, preferably 240 r / min.
[0045] In addition, the present invention also provides an application of an environmentally friendly conductive cement-based material curing agent, and the application of the environmentally friendly conductive cement-based material curing agent in the preparation of cured soil.
[0046] The introduction of modified lithium slag powder and carbon fiber into the curing agent can effectively improve the conductivity and crack resistance (stability) of the solidified soil. During winter construction, a micro-current can be passed through the solidified soil to effectively increase the internal temperature of the solidified soil, thereby increasing the hydration rate of the solidified soil and shortening the construction period. At the same time, the addition of carbon fiber can not only effectively improve the conductivity of the modified lithium slag powder, but also improve the crack resistance of the solidified soil, thereby improving the stability of the solidified soil.
[0047] Furthermore, the environmentally friendly conductive cement-based material curing agent is mixed with sludge to obtain solidified soil, and the specific steps are as follows:
[0048] The environmentally friendly conductive cement-based material curing agent is mixed with the sludge, stirred evenly, and cured at room temperature for a period of time to obtain the cured soil.
[0049] Furthermore, the mass ratio of the environmentally friendly conductive cement-based material curing agent to the sludge is 1:(3-8);
[0050] The resting time is 3-7 days.
[0051] The principle of the present invention is as follows:
[0052] Lithium slag contains residual lithium compounds (Li2CO3), which can be modified to increase the content of lithium oxide inside it, thereby making it have a certain conductivity. The modified lithium slag powder is obtained by acidifying and calcining the lithium slag and finally grinding it. The lithium salt (Li2CO3) in the lithium slag is then reacted in a hydrochloric acid solution environment to generate lithium chloride. The solution after the reaction is then evaporated and crystallized. The crystals obtained by evaporation are fully reacted with carbonic acid to obtain purified lithium carbonate. Finally, the lithium slag containing lithium carbonate is calcined at 1000°C to decompose the lithium carbonate to obtain lithium oxide. At the same time, the calcium, aluminum and other salts contained inside are decomposed to generate alkaline oxides such as calcium oxide and aluminum. Finally, it is ground to obtain modified lithium slag powder. The specific chemical reaction is shown in the following formula:
[0053]
[0054]
[0055] In addition, in the field of alkali-activated building materials, the strength and crack resistance of alkali-activated geopolymers are much better than those of ordinary concrete, but due to the low calcium oxide content in lithium slag, the strength and crack resistance of alkali-activated geopolymers are far from enough. Based on the above situation, the "calcium supplementation" measure (i.e., CaO supplementation of lithium slag powder) can effectively improve the strength and crack resistance of lithium slag powder alkali-activated geopolymer cementitious materials. Therefore, the "calcium supplementation" measure can effectively improve the application of lithium slag in the field of building materials.
[0056] Lithium slag powder can improve the strength of its alkali-activated geopolymer by "calcium supplementation", and the CaO content in the regenerated micropowder is relatively high. Therefore, by adjusting the amount of regenerated micropowder in the composite alkali-activated raw materials (modified carbide slag, regenerated micropowder), the modified carbide slag powder can obtain the effect of "calcium supplementation", thereby improving the activation effect of the modified carbide slag powder in the composite alkali-activated raw materials in an alkaline environment, and improving the strength and crack resistance of the overall solidified soil.
[0057] The present invention uses recycled micropowder as a "calcium supplement" for lithium slag alkali-activated geopolymer. Recycled micropowder is a powdered construction waste with a particle size of ≤0.16 mm that is generated during the particle shaping process of construction solid waste and collected by a dust collector. Its chemical composition is mainly CaO. Therefore, the use of recycled aggregate can not only give full play to its own properties to improve the strength and crack resistance of lithium slag alkali-activated geopolymer, but also effectively improve the utilization rate of construction solid waste, and gradually eliminate the environmental pollution problems caused by the large-scale accumulation of industrial solid waste.
[0058] The introduction of modified lithium slag powder and carbon fiber into the curing agent can effectively improve the conductivity and crack resistance (stability) of the solidified soil. During winter construction, a micro-current can be passed through the solidified soil to effectively increase the internal temperature of the solidified soil, thereby increasing the hydration rate of the solidified soil and shortening the construction period. At the same time, the addition of carbon fiber can not only effectively improve the conductivity of the modified lithium slag powder, but also improve the crack resistance of the solidified soil, thereby improving the stability of the solidified soil.
[0059] The alkaline activator of the present invention comprises sodium hydroxide, water glass, etc. As an alkaline activator, sodium hydroxide provides an alkaline environment during the hydration reaction and promotes the reaction to proceed in the positive direction.
[0060] The internal hydration of the solidified soil in the present invention includes an alkali-induced reaction, which has the effects of adjustable reaction rate and better anti-cracking performance. The internal reaction rate can be effectively increased during winter construction, and the hydration degree of the solidified soil can be reduced by adjusting the alkali-induced reaction process during summer construction, thereby reducing the possibility of cracking caused by excessive hydration rate.
[0061] The present invention organically combines and utilizes the physical and chemical properties of industrial wastes to achieve the purpose of turning waste into treasure. First, starting from the fact that the modified lithium slag in the solidified soil can provide a certain conductivity, the conductivity of the solidified soil containing the modified lithium slag is optimized and improved by utilizing the properties of carbon fiber with low resistivity and high conductivity. The improvement of conductivity can increase the overall temperature of the solidified soil by conduction during winter construction, thereby alleviating the problem of slow hydration speed due to low external temperature. In addition, the addition of carbon fiber can also improve the anti-cracking performance of the solidified soil, thereby ensuring the strength and stability of the solidified soil. Secondly, the cement-based curing agent contains recycled micropowder, which can act as an external calcium source to supplement the modified lithium slag powder, so that the modified lithium slag powder can obtain the effect of "calcium supplementation", increase the CaO content in the overall alkali-activated raw materials, and then improve the activation effect of the modified lithium slag powder in the composite alkali-activated raw materials in an alkaline environment, and the strength can be quickly and effectively improved; finally, due to the outstanding advantages of alkali activation such as small water demand, low hydration heat, good thermal stability, high crack resistance and water reduction, and fast hydration process, therefore, introducing some alkali-activated materials in the preparation process of the curing agent will further optimize the crack resistance of the cured soil and shorten the hydration and hardening time of the cured soil.
[0062] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0063] 1. Due to the chemical composition of lithium slag itself, it is impossible to apply it to alkali-activated materials. Here, by taking "calcium supplementation" measures (i.e., supplementing CaO to lithium slag) and adjusting the amount of "calcium supplementation", the activation effect of lithium slag in an alkaline environment is improved, thereby improving the strength and crack resistance of lithium slag alkali-activated geopolymer cementitious materials, and realizing and improving the application of lithium slag in the construction field; in addition, the present invention uses recycled micropowder as the "calcium supplementation" material for lithium slag alkali-activated geopolymer, which not only effectively utilizes the high "CaO" content in the recycled micropowder, but also improves the utilization of recycled aggregates.
[0064] 2. Compared with the existing cement-based curing agent, the curing agent of the present invention introduces modified lithium slag powder and carbon fiber to effectively improve the conductivity and crack resistance (stability) of the solidified soil. During winter construction, a microcurrent can be passed through the solidified soil to effectively increase the internal temperature of the solidified soil, thereby increasing the hydration rate of the solidified soil and shortening the construction period; during summer construction, the cracking caused by the excessive hydration and hardening of the solidified soil can be controlled and alleviated by adjusting the alkali-induced hydration reaction rate; at the same time, the addition of carbon fiber can not only effectively improve the conductivity of the modified lithium slag powder, but also improve the crack resistance of the solidified soil, thereby improving its stability.
[0065] 3. The preparation process of the present invention uses industrial waste as the main raw material to prepare cement-based material curing agent, realizes the replacement of cement materials, reduces the amount of cement materials in cement-based curing agent, can not only alleviate the excessive consumption of limestone, clay and energy in cement production, reduce the high energy consumption and high pollution problems caused by cement production, but also can gradually eliminate the environmental pollution problems caused by the large accumulation of industrial solid waste. It meets the requirements of national environmental protection policies and has great application prospects. DETAILED DESCRIPTION
[0066] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0067] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All reagents used were conventional products that can be purchased commercially.
[0068] In the following, some embodiments of the present invention are described in detail in conjunction with specific embodiments. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0069] Example 1
[0070] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0071] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0072] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0073] Then, 200 parts by weight of cement, 20 parts by weight of modified lithium slag powder, 180 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0074] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0075] Example 2
[0076] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0077] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0078] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0079] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0080] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0081] Example 3
[0082] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0083] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0084] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0085] Then, 200 parts by weight of cement, 40 parts by weight of modified lithium slag powder, 160 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0086] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0087] Example 4
[0088] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0089] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0090] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0091] Then, 200 parts by weight of cement, 50 parts by weight of modified lithium slag powder, 150 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0092] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0093] Example 5
[0094] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0095] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0096] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0097] Then, 200 parts by weight of cement, 60 parts by weight of modified lithium slag powder, 140 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0098] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0099] Example 6
[0100] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0101] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0102] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0103] Then, 200 parts by weight of cement, 70 parts by weight of modified lithium slag powder, 130 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0104] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0105] Example 7
[0106] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0107] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0108] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0109] Then, 200 parts by weight of cement, 80 parts by weight of modified lithium slag powder, 120 parts by weight of recycled micro powder and 2 parts by weight of carbon fiber are mixed to obtain a raw material;
[0110] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0111] Example 8
[0112] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0113] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0114] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0115] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 0.5 parts by weight of carbon fiber are mixed to obtain a raw material;
[0116] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0117] Example 9
[0118] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0119] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0120] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0121] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 1 part by weight of carbon fiber are mixed to obtain a raw material;
[0122] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0123] Example 10
[0124] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0125] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0126] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0127] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 1.5 parts by weight of carbon fiber are mixed to obtain a raw material;
[0128] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0129] Embodiment 11
[0130] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0131] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0132] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0133] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 2.5 parts by weight of carbon fiber are mixed to obtain a raw material;
[0134] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0135] Example 12
[0136] This embodiment provides an environmentally friendly conductive cement-based material curing agent, and the components and weight portions of the environmentally friendly conductive cement-based material curing agent are shown in Table 1.
[0137] In addition, this embodiment also provides a method for preparing an environmentally friendly conductive cement-based material curing agent, and the specific steps are as follows:
[0138] First, 40 parts of sodium hydroxide, 200 parts of water glass and 15 parts of water are stirred, dissolved and cooled to prepare an alkaline activator solution;
[0139] Then, 200 parts by weight of cement, 30 parts by weight of modified lithium slag powder, 170 parts by weight of recycled micro powder and 3.0 parts by weight of carbon fiber are mixed to obtain a raw material;
[0140] The alkaline activator solution is poured into the mixed raw materials and stirred to obtain an environmentally friendly conductive cement-based material curing agent.
[0141] The environmentally friendly conductive cement-based material curing agent obtained in Examples 1 to 12 is used to perform in-situ curing treatment on the in-situ soil, and the specific steps are as follows:
[0142] The in-situ soil is mixed by direct insertion of a mixing device; the mixing device runs forward to gradually mix deeply and spray the curing agent until it reaches the designed bottom of the solidification; the rate of stirring lifting or lowering is controlled at 22s / m, and the spraying rate of the curing agent is controlled at 100Kg / min; the mixing device runs in reverse to slowly lift, stir and spray the curing agent; the mixing time of each small block is controlled at 8min, and each small block is stirred up and down 3 times each. The first 2 times are stirred while spraying, and the third time is only stirred without spraying. After each small block is stirred, it is stirred as a whole again to ensure uniform mixing within the block; a fixed mark is made on the mixing head, and when the mixing head stirs downward to the mark line, it indicates that the mixing depth has reached the designed solidification depth.
[0143] After the curing construction, heavy-duty dynamic penetration was performed on randomly selected points of each dosage test block. The heavy-duty dynamic penetration test method and measured data are as follows:
[0144] The heavy-duty dynamic penetration test adopts the crossbeam platform loading method. Three steel beams are used to build a platform, and 1m×1m×3m counterweight blocks are placed on the platform, a total of 6 blocks, with a total counterweight of 300kN; the load plate size is 7m×0.5m; the load is applied using a 2MN manual hydraulic jack; the load is measured using a 20MPa hydraulic gauge; the settlement is measured using two 50mm dial indicators, symmetrically installed on both sides of the load plate.
[0145] The specific test ratios and test results are shown in Tables 1-3:
[0146] Table 1 Specific test ratios of each embodiment
[0147] Example cement Modified lithium slag powder Recycled Micro Powder Carbon Fiber Water Glass Sodium hydroxide water 1 200 20 180 2 200 40 15 2 200 30 170 2 200 40 15 3 200 40 160 2 200 40 15 4 200 50 150 2 200 40 15 5 200 60 140 2 200 40 15 6 200 70 130 2 200 40 15 7 200 80 120 2 200 40 15 8 200 30 170 0.5 200 40 15 9 200 30 170 1 200 40 15 10 200 30 170 1.5 200 40 15 11 200 30 170 2.5 200 40 15 12 200 30 170 3.0 200 40 15
[0148] Note: The concentration of water glass used in the present invention is 40%.
[0149] Table 2 Statistical table of heavy-duty dynamic penetration results:
[0150]
[0151]
[0152] Table 2 is a statistical list of heavy-duty dynamic probing results for each group of embodiments. It can be seen that the measured number of hammer strikes for each group of embodiments shows a trend of first increasing and then decreasing as the curing depth continues to increase. At the same time, further analysis found that, overall, the measured number of hammer strikes for Example 2 at each curing depth is the highest, and the performance is the best, indicating that its curing effect is the best at this time. In addition, as the ratio of modified lithium slag to recycled micropowder gradually decreases, the curing effect of the cured soil gradually decreases; by observing Examples 2 and 8-12, it can be seen that as the amount of carbon fiber added gradually increases, the curing effect of the cured soil shows a phenomenon of first increasing and then weakening.
[0153] With reference to the standard of GB / T 17671-1999, the compressive strength and flexural strength tests of cement foundation material samples were carried out using cement compressive strength testing machine and cement electric flexural testing machine. The sample size was 50mm×50mm×200mm, with 5 pieces in each group. The cement foundation material samples were cured after demoulding, and the compressive strength and flexural strength tests were carried out again after reaching the specified age.
[0154] Table 3 Mechanical properties and electrical conductivity test table
[0155]
[0156]
[0157] Table 3 is a statistical test result of mechanical properties and electrical conductivity of each group of embodiments. According to embodiments 1-7, it can be seen that the compressive strength and flexural strength of each group of embodiments show a trend of first increasing and then decreasing as the ratio of modified lithium slag to regenerated micropowder gradually decreases. Among them, the compressive strength and flexural strength of embodiment 2 are the best in general. In terms of electrical conductivity, according to the analysis of embodiments 1-7, it can be seen that as the ratio of modified lithium slag to regenerated micropowder gradually increases, its resistivity continues to decrease, that is, the electrical conductivity gradually increases. At the same time, according to the analysis of embodiments 2 and 8-12, it can be seen that as the carbon fiber content continues to increase, the electrical conductivity of the solidified soil also continues to increase.
[0158] The present invention uses cement, modified lithium slag powder, and regenerated micropowder as the main components of cement curing agent, and uses carbon fiber as an additive to form a cement-based material curing agent together with cement, modified lithium slag powder, and regenerated micropowder. The addition of modified lithium slag powder can make the solidified soil have a certain conductivity, and the addition of carbon fiber can effectively improve the conductivity of the solidified soil, and can enhance the anti-cracking performance of the solidified soil, thereby improving the strength and stability of the solidified soil. In addition, the regenerated micropowder contains a high content of calcium oxide, which can serve as an external calcium source to supplement the modified lithium slag powder, and then under the action of alkali excitation, the strength can be quickly and effectively improved. The preparation process of the present invention uses industrial waste as the main raw material to prepare a cement-based material curing agent, realizes the replacement of cement materials, reduces the amount of cement materials in the cement-based curing agent, can not only alleviate the excessive consumption of limestone, clay and energy in cement production, reduce the high energy consumption and high pollution problems caused by cement production, but also can gradually eliminate the environmental pollution problems caused by the large-scale accumulation of industrial solid waste. It meets the requirements of national environmental protection policies and has great application prospects.
[0159] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An environmentally friendly conductive cement-based material curing agent, characterized in that: The composition comprises the following components in parts by weight: 150-250 parts of cement, Modified lithium slag powder 20-100 parts, Recycled micro powder 120-200 parts, Carbon fiber 0.5-3 parts, 210-270 parts of activator, 10-20 parts water; The modified lithium slag powder comprises the following components by mass percentage: CaO 60-65%, MgO 1-2%, SiO2 5-10%, Li2O 2%-3%, Fe2O3 0.5%-2.0%, Al2O3 0.1%-1.0% and inevitable impurities, the sum of the mass percentages of CaO, MgO, SiO2, Fe2O3, Al2O3, Li2O and impurities is 100%; The specific steps of the method for preparing the environmentally friendly conductive cement-based material curing agent are as follows: S1, the waste lithium slag after producing lithium carbonate is successively subjected to hydrochloric acid acidification, evaporation crystallization, carbonic acid purification, calcination, and finally grinding to prepare modified lithium slag powder; S2. Weigh cement, modified lithium slag powder, recycled micro powder, carbon fiber, activator and water according to the mix ratio; S3, stirring and dissolving the activator and water to obtain an activator solution; S4, mixing cement, modified lithium slag powder, recycled micro powder and carbon fiber to obtain raw materials; S5. Stir and mix the activator solution obtained in step S3 and the raw materials obtained in step S4 to obtain an environmentally friendly conductive cement-based material curing agent.
2. The environmentally friendly conductive cement-based material curing agent according to claim 1, characterized in that: The cement used is P·O 42.5 cement, 300m 2 / kg≤Specific surface area≤370m 2 / kg; The average particle diameter of the modified lithium slag powder is 20-50 μm.
3. The environmentally friendly conductive cement-based material curing agent according to claim 1, characterized in that: The regenerated micro powder is powdered construction waste with a particle size of ≤0.16 mm generated during the particle shaping process of construction solid waste and collected by a dust collector. The regenerated micro powder is composed of crushed pieces of mountain-hardened cement stone, coarse aggregate and fine aggregate.
4. The environmentally friendly conductive cement-based material curing agent according to claim 3, characterized in that: The regenerated micro powder comprises the following components by mass percentage: CaO 45-50%, MgO 1-2%, SiO2 30-35%, Fe2O3 2%-4.0%, Al2O3 5%-10% and inevitable impurities, the sum of the mass percentages of CaO, MgO, SiO2, Fe2O3, Al2O3 and impurities is 100%.
5. The environmentally friendly conductive cement-based material curing agent according to claim 1, characterized in that: The carbon fiber has a carbon content of more than 90%, a diameter range of 5-10 microns, and a resistivity range of 2×10 -6 Ω·cm.
6. The environmentally friendly conductive cement-based material curing agent according to claim 1, characterized in that: The exciter is composed of the following components in parts by weight: 30-50 parts of sodium hydroxide, 180-220 parts of water glass.
7. The environmentally friendly conductive cement-based material curing agent according to claim 1, characterized in that: The calcination temperature is 1000-1400°C.
8. Application of an environmentally friendly conductive cement-based material curing agent, characterized in that: Use of the environmentally friendly conductive cement-based material curing agent as described in any one of claims 1 to 7 in the preparation of cured soil.
Citation Information
Patent Citations
Low-carbon cement prepared from modified lithium slag composite multi-source solid waste, and method and application thereof
CN117069400A
Lithium slag-based concrete mineral admixture
CN111732358A
Electrically conductive cement-based composite composition
US20190284094A1